Investment dispute management: The importance of the domestic dimension - Alejandro Carballo; Frauke Nitschke (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2022)
This Perspective highlights the two key elements that governments need to consider at the domestic level to effectively manage investment disputes, independently of any reform of the investor-state dispute-settlement (ISDS) mechanism. Such a domestic framework increases stakeholders' confidence, strengthens FDI retention and enables countries to be proactive and save resources.
Keywords: 330